DYSLIPIDEMIA AS AN ADVERSE RISK FACTOR FOR CORONARY HEART DISEASE IN YOUNG MEN - Khasanjanova F. O. (Scholar Express Journals, 2023)
The clinical status of patients with coronary heart disease (CHD) and its relationship with atherogenic and anti-atherogenic lipoproteins was studied. We examined 230 patients with CHD aged 18 to 74 years (mean age 52.0±5.0 years). All the patients underwent history taking, anthropometry, general clinical, laboratory, biochemical (lipid spectrum) and instrumental studies. Obtained lipid profile analyses in patients with IHD showed that LDL in the 1st and 2nd groups were almost equally elevated compared to the control group.
Keywords: CHD; young; age